The Influence of Social Media Emotions: Evidence from the Kodak Manic Episode - Cioroianu, I.; Conlon, T.; Corbet, S.; Larkin, C.; Oxley, Leslie; Taffler, R. (Taylor & Francis Group, 2024)
This paper explores the impact of Kodak’s announcements of ventures into the cryptocurrency and pharmaceutical industries on market sentiment and investor emotions. Evaluating social media data using novel sentiment analysis techniques, we find that emotions such as excitement, mania, anxiety, panic, and revulsion were salient in response to the announcements of KodakCoin and KodakPharma. Our results suggest that these emotions had significant short-term effects on share prices and market perception, demonstrating the impact of emotional patterns observed within KodakCoin and KodakPharma events on investor behavior and emphasizing the vulnerability of unsophisticated online stock traders to corporate ‘pivots’ irrespective of the perceived associated risks. We highlight the significance of monitoring emerging technologies and balancing innovation with stability, contributing to developing a more resilient financial ecosystem. Furthermore, this research underscores the importance of addressing several key areas in policy and regulation to ensure a stable and transparent financial ecosystem.